Prescribing Patterns of Oral Antibiotics and Isotretinoin for Acne in a Colorado Hospital System: Retrospective Cohort Study - Madeline J Adelman; Torunn E Sivesind; Isaac Weber; Grace Bosma; Camille Hochheimer; Chante Karimkhani; Lisa M Schilling; John S Barbieri; Robert P Dellavalle (JMIR Publications, 2023)
BackgroundGuidelines established by the American Academy of Dermatology recommend oral antibiotics as first-line therapy for mild, moderate, and severe acne. However, it is recommended to minimize the duration of oral antibiotic use, and there is increasing support for other systemic agents for acne. ObjectiveWe sought to characterize the use of oral antibiotics and isotretinoin for the treatment of acne in the pediatric and young adult population aged 10 through 20 years and the adult population aged 21 to 45 years from 2011 to 2019. MethodsWe conducted a retrospective, observational cohort study using electronic data from the enterprise data warehouse of the University of Colorado Anschutz Medical Campus and its affiliates, with data in the format of the Observational Health Data Sciences and Informatics (OHDSI) Observational Medical Outcomes Partnership (OMOP) common data model. Categorical values (sex, race, and ethnicity) were compared using chi-square tests, and continuous variables (age) were compared using 2-tailed t tests. ResultsOur cohort of 15,704 patients was composed of mostly White (12,776/15,704, 81.4%), non-Hispanic or Latino (13,307/15,704, 84.7%), and female (11,093/15,704, 70.6%) patients. Among the 4605 male patients in the eligible cohort, 1810 (39%) received an oral antibiotic treatment, in comparison to 3109 (28%) of the 11,093 eligible women (P<.001). Among the 4605 men who were eligible for treatment with isotretinoin in this population, 988 (21.5%) received a course of isotretinoin, compared to only 10.4% (1159/11,093) eligible women (P<.001). Male patients were 1.67 times more likely to have received an antibiotic prescription (odds ratio [OR] 1.67, 95% CI 1.55-1.79) and over twice as likely to have received an isotretinoin prescription (OR 2.34, 95% CI 2.13-2.57) than female patients. ConclusionsMinocycline was the most frequently prescribed antibiotic for the treatment of acne in this study cohort. From 2015 to 2019, there was no significant change in the number of antibiotic prescriptions over time. Men were significantly more likely to receive both oral antibiotics and isotretinoin than female patients. Multiple factors could be contributing to this discrepancy, including the burden of iPLEDGE, additional systemic treatment options for female patients, and the difference in acne severity across sexes. We could not determine the difference in severity of acne between male and female patients in our cohort, and further research is needed to ascertain the variation across sexes.